Рефлексивы в прусском языке - Geniušienė, Ema (Baltistica, 1981)
Reflexives in Old Prussian This paper deals with the derivational history of Old Prussian reflexives and their syntactic and semantic properties. The reflexives fall into three semantic classes: reflexives proper, self-move and dative reflexives.